Allele Frequencies of Apolipoprotein E in a South Western Nigerian population on HAART - Olabisi Titilayo BAMIDELE; Olatunde Olayanju; Martin Ehizode Emuze; Joel Olufunminiyi Akande; Nonso Nduka; Bola Joyce Eseile; Olanrewaju Olasehinde; Modupe Akinrele Kuti (Babcock University Medical Journal, 2022)
Objective: Increasing evidence has shown that ApoE polymorphism is associated with the early onset of cardiovascular and neurological diseases in patients on HAART. The frequency of occurrence of the alleles and the genotypes vary by race and population. The study describes the pattern seen among adults in Ibadan, Nigeria.